Implications of climate crisis in Southern Africa - Maviza, Gracsious; Nzima, Divane; Gadu, Ernest Siyaxola; Ndlovu, Ntobeko (Springer, 2025)
This chapter discusses climate crisis within the framework of climate capitalism. Contrary to the conventional understanding of climate from an anthropocentric perspective, the discussion here emphasises fairness, equity, and inclusivity in crafting solutions that recognise the role of the history of colonialism and imperialism perpetuated by powerful countries and multinational corporations. Chapter concludes that only comprehensive strategies prioritising sustainability and inclusivity, beyond market-driven approaches will help build a more just and resilient future for Africa.